Correction: Li et al. Extraction of Polysaccharides from Root of Pseudostellaria heterophylla (Miq.) Pax. and the Effects of Ultrasound Treatment on Its Properties and Antioxidant and Immune Activities. Molecules 2024, 29, 142 - Hangyu Li; Ziwei Liu; Qianqian Liu; Xinnan Zhang; Sheng Li; Feng Tang; Linzi Zhang; Qian Yang; Qiran Wang; Shuyao Yang; Ling Huang; Yuwei Ba; et al. (Molecules)
Errors in Figure [...]